Aspects related to floral morphology and pollen viability for the pollination of self-compatible and self-incompatible pitaya species - Santos, Nubia Cassiana; Cruz, Maria do Céu Monteiro; Sena, Cintia Gonçalves; Alves , Deilson de Almeida; Guimarães, Amanda Gonçalves; Abreu, Caique Menezes de (Acta Scientiarum. Agronomy, 2026)
Pitaya species can be self-compatible, partially self-compatible, or self-incompatible. Information related to floral biology and pollination is important for identifying the causes of self-incompatibility and the factors that limit self-pollination among pitaya species. This research was carried out to evaluate floral morphology, pollen viability, stigma receptivity, and different pollination methods in genotypes of Selenicereus undatus and S. monacanthus. During the flowering period, the flower buds were selected, identified, and protected in the pre-anthesis stage to evaluate floral morphology, pollen viability, and pollen transfer methods at the time of anthesis. The genotypes had complete flowers and showed differences in floral morphology related to the quantity and coloration of the protective tissues of the flower buds. Herkogamy was more pronounced in S. monacanthus. Anthesis in both species was coincident, with a longer duration in S. undatus. During anthesis, both species presented receptive stigmas and viable pollen grains, with dehiscent anthers before the flowers opened. The S. monacanthus genotype was self-incompatible. Seeds from self-pollination showed lower germination. Manual cross-pollination between the genotypes promoted a high fruit set and the formation of fruit of a high commercial standard.